Time‐to‐onset analysis of amiodarone‐associated thyroid dysfunction. (10th August 2019) - Kinoshita, Sayoko; Hosomi, Kouichi; Yokoyama, Satoshi; Takada, Mitsutaka
Abstract: What is known and objective: Amiodarone (AMD) treatment is associated with a number of significant adverse effects including thyroid dysfunction. However, the relationship between the development of thyroid dysfunction and the dosage and treatment duration of AMD remains unclear. The purpose of this study was to examine the onset profiles of amiodarone‐associated thyroid dysfunction using a spontaneous adverse drug reaction (ADR) reporting database. Methods: Data were obtained from the US Food and Drug Administration Adverse Event Reporting System (FAERS). For signal detection of spontaneous ADRs, the reporting odds ratio (ROR) and information component (IC) were calculated. Cumulative incidences of hyperthyroidism and hypothyroidism were assessed using the Kaplan‐Meier method, and time‐to‐onset profiles were analysed using the Weibull shape parameter (WSP) test. Results and discussion: The median time‐to‐onset of hyperthyroidism associated with AMD and other drugs was 720.0 (range: 225.5‐1145.0) and 101.5 (range: 14.0‐468.8) days, respectively. Patients treated with AMD showed a significantly longer time‐to‐onset of hyperthyroidism than those treated with other drugs ( P  < .001). The median time‐to‐onset of hypothyroidism associated with AMD and other drugs was 183.0 (range: 35.0‐727.8) and 153.0 (range: 19.0‐608.0) days, respectively. There was no significant difference in the time‐to‐onset of hypothyroidism between patients treated with AMD and those treated with other drugs ( P  = .13). For hyperthyroidism, the WSP test showed that AMD had a wear‐out failure‐type profile and other drugs had early failure‐type profiles. For hypothyroidism, the WSP test showed that both AMD and other drugs had early failure‐type profiles. What is new and conclusions: Amiodarone‐associated hyperthyroidism had a different onset profile than hyperthyroidism associated with other drugs. Because the time‐to‐onset of AMD‐associated hyperthyroidism is widely distributed, sustained and continuous attention is required to detect and treat hyperthyroidism during AMD treatment. In contrast, AMD‐associated hypothyroidism had an onset profile that was similar to that of other drugs, suggesting that attention should be focused on the earlier stages of treatment. Abstract : AMD‐associated hyperthyroidism had a different onset profile than hyperthyroidism associated with other drugs. In contrast, AMD‐associated hypothyroidism had an onset profile that was similar to that of other drugs.